Loneliness and Fear of COVID-19 in Polish Adults. The Mediating Role of Generalized Mood - Agnieszka Ewa Lewicka Zelent; Paweł Brudek; Marta Czechowska-Bieluga (Journal of Modern Science, 2022)
Objectives Since the end of 2019 the COVID-19 pandemic has been determining the ways in which nations, institutions, and individuals function. As of now, despite a growing body of research, little is known about the effects of the pandemic in the area of psychosocial functioning of an individual. An analysis of the results of the studies conducted so far implies that the feeling of loneliness, caused or exacerbated by pandemic regimes, may increase fear of COVID-19. To provide effective psychological support to persons suffering from fear of the coronavirus relationships between the feeling of loneliness and fear of the COVID-19 must be understood. Both clinical experience and research results show that generalized mood may be a mediator in the postulated relationships. The present work studies the relationship between loneliness and fear of COVID-19, and the generalized mood as a mediator in this relationship in adults.